Nonstandard Work Hours and Single Versus Coupled Mothers' Work‐to‐Family Conflict. Issue 2 (6th March 2019) - Moilanen, Sanna; Aunola, Kaisa; May, Vanessa; Sevón, Eija; Laakso, Marja‐Leena
Abstract : Objective: To compare single and coupled mothers' experiences of time‐based work‐to‐family conflict (WFC) and work‐to‐family positive affective spillover (PAS) in the context of maternal nonstandard work hours. Background: Despite having become one of the central topics of work–family research, studies examining the relationship of maternal work schedules and family roles have mainly focused on North American samples or dual‐earner families. Although qualitative studies have highlighted the problems faced by European single mothers in relation to the combination of nonstandard work hours and family life, there are no quantitative or cross‐national comparative studies on the association. Method: Using a convenience sample derived from the Families 24/7 survey of Finnish, Dutch, and British mothers with children 12 years of age or younger ( N = 1, 106), path analysis was carried out to assess the associations of single motherhood, nonstandard work hours, and their interaction with WFC and PAS and to compare the associations between 3 countries. Results: The positive association between the amount of nonstandard work hours and WFC was found to be stronger among single mothers than coupled mothers in all 3 countries. However, in Finland, both single and coupled mothers, and in the Netherlands and the United Kingdom, only single mothers, experienced higher WFC when the mother worked more during nonstandard hours. In all countries, single mothers experienced less PAS than coupled mothers. Conclusion: Dutch and British single mothers who work nonstandard hours experience the combination of multiple roles particularly challenging compared with coupled mothers. In Finland, both single and coupled mothers report high levels of WFC when they work more nonstandard hours; hence, a greater amount of work during nonstandard hours is not an automatic indication of heightened challenges for single mothers alone. Implications: When aiming to improve mothers' work–family reconciliation via social and workplace policies, it is important to understand the circumstances of single and coupled mothers in different cultural contexts.